2022
DOI: 10.3390/met12111913
|View full text |Cite
|
Sign up to set email alerts
|

On the Microstructure Development under Cyclic Temperature Conditions during WAAM of Microalloyed Steels

Abstract: This paper shed light on the kinetics of transformation and the developed microstructure during wire arc additive manufacturing (WAAM). Three microalloyed alloys, two of them are high strength low alloyed steel (HSLA) grades and the third is a Ni-Cr-Mo steel, from which the welding wires are being produced, were investigated. Repeated cycles around varied temperatures from a reheating temperature of 1350 °C and down to a temperature 35 °C below the Ae1 are applied using dilatometer on samples from the steels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In essence, a robust process window is the key to unlocking the full potential of medium-manganese steels in industrial praxis. Huang et al [8] highlighted the dependence of microstructure development on the alloying composition and thermal cycling parameters during wire arc additive manufacturing (WAAM). They suggested that the HSLA steels are more suitable for producing softer and consequently tougher components than that produced from the conventional welding wires.…”
Section: Contributionsmentioning
confidence: 99%
“…In essence, a robust process window is the key to unlocking the full potential of medium-manganese steels in industrial praxis. Huang et al [8] highlighted the dependence of microstructure development on the alloying composition and thermal cycling parameters during wire arc additive manufacturing (WAAM). They suggested that the HSLA steels are more suitable for producing softer and consequently tougher components than that produced from the conventional welding wires.…”
Section: Contributionsmentioning
confidence: 99%
“…The subsequent heating cycle and the corresponding peak temperature determine whether these child phases transform back to the parent austenite phase. In steels, the critical 𝐴𝑐 3 temperature is the temperature above which all child phases transform back to the parent phase completely [21,22,18]. This critical temperature is hence termed the reset temperature in the remainder and is indicated in Fig.…”
Section: Introductionmentioning
confidence: 99%